2022
DOI: 10.1002/qute.202200001
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Color Passively Q‐Switched Raman Microchip Laser with Tunable Power Intensity Ratio and Elliptical Polarization

Abstract: Elliptically polarized high peak power two‐color lasers have potential applications on material science, biology, optical detection, and terahertz wave generation. Two‐color pulsed lasers with flexible power intensity ratio are essential for analyzing material properties, however, control of power ratio between two lasers is a challenge for developing compact passively Q‐switched (PQS) solid‐state laser. Here, taking advantage of Nd:YAG/Cr4+:YAG composite crystal and a‐cut YVO4 crystal, a PQS Raman microchip l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It should be mentioned that 1064‐nm laser can be easily frequency‐doubled to 532 nm for imaging hemoglobin [28], or extends to 1.2‐μm region by Raman crystal for identifying lipid [35]. This feature enables the PQS‐SSL suitable for functional PAM.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that 1064‐nm laser can be easily frequency‐doubled to 532 nm for imaging hemoglobin [28], or extends to 1.2‐μm region by Raman crystal for identifying lipid [35]. This feature enables the PQS‐SSL suitable for functional PAM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Moreover, laser spectral bandwidth has been expanded with SRS effect [ 20,22 ] and SoP has been manipulated with anisotropy of vanadate crystals. [ 23,24 ] Recently, n × n vortex arrays have been converted from petal‐like Raman lasers constructed with Yb:YAG and c ‐cut YVO 4 crystals. [ 25,26 ] It has been demonstrated that the SoP of cylindrical vector vortex beams can be controlled with thermal effect induced local birefringence in annular beam pumped microchip lasers.…”
Section: Introductionmentioning
confidence: 99%